Ketones and lactate "fuel" tumor growth and metastasis: Evidence that epithelial cancer cells use oxidative mitochondrial metabolism - Bonuccelli, Gloria; Tsirigos, Aristotelis; Whitaker-Menezes, Diana; Pavlides, Stephanos; Pestell, Richard G.; Chiavarina, Barbara; Frank, Philippe G.; Flomenberg, Neal; Howell, Anthony; Martinez-Outschoorn, Ubaldo E.; Sotgia, Federica; Lisanti, Michael P. (Cell cycle (Georgetown, Tex.), 2010)
Previously, we proposed a new model for understanding the "Warburg effect" in tumor metabolism. In this scheme, cancer-associated fibroblasts undergo aerobic glycolysis and the resulting energy-rich metabolites are then transferred to epithelial cancer cells, where they enter the TCA cycle, resulting in high ATP production via oxidative phosphorylation. We have termed this new paradigm "The Reverse Warburg Effect." Here, we directly evaluate whether the end-products of aerobic glycolysis (3-hydroxy-butyrate and L-lactate) can stimulate tumor growth and metastasis, using MDA-MB-231 breast cancer xenografts as a model system. More specifically, we show that administration of 3-hydroxy-butyrate (a ketone body) increases tumor growth by ~2.5-fold, without any measurable increases in tumor vascularization/angiogenesis. Both 3-hydroxy-butyrate and L-lactate functioned as chemo-attractants, stimulating the migration of epithelial cancer cells. Although L-lactate did not increase primary tumor growth, it stimulated the formation of lung metastases by ~10-fold. Thus, we conclude that ketones and lactate fuel tumor growth and metastasis, providing functional evidence to support the "Reverse Warburg Effect." Moreover, we discuss the possibility that it may be unwise to use lactate-containing i.v. solutions (such as Lactated Ringer's or Hartmann's solution) in cancer patients, given the dramatic metastasis-promoting properties of L-lactate. Also, we provide evidence for the up-regulation of oxidative mitochondrial metabolism and the TCA cycle in human breast cancer cells in vivo, via an informatics analysis of the existing raw transcriptional profiles of epithelial breast cancer cells and adjacent stromal cells. Lastly, our findings may explain why diabetic patients have an increased incidence of cancer, due to increased ketone production, and a tendency towards autophagy/mitophagy in their adipose tissue.